Case Report: Susceptibility to viral infections and secondary hemophagocytic lymphohistiocytosis responsive to intravenous immunoglobulin as primary manifestations of adenosine deaminase 2 deficiency - Drago, Enrico; Garbarino, Francesca; Signa, Sara; Grossi, Alice; Schena, Francesca; Penco, Federica; Santori, Elettra; Candotti, Fabio; Boztug, Kaan; Volpi, Stefano; Gattorno, Marco; Caorsi, Roberta (Frontiers in Immunology, 2022)
Deficiency of Adenosine Deaminase 2 (DADA2) is an autosomal recessive disease associated with a highly variable clinical presentation, including systemic vasculitis, immunodeficiency and cytopenia. We report a case of a 16-year-old girl affected by recurrent viral infections (including CMV-related hepatitis and measles vaccine virus-associated manifestations) and persistent inflammation, occurred after Parvovirus infection and complicated by secondary hemophagocytic lymphohistocytosis (HLH). HLH first episode presented at 6 years of age and was preceded by persistent fever and arthralgias with evidence of Parvovirus B19 infection. The episode responded to intravenous steroids but relapsed during steroids tapering. High dose intravenous immunoglobulin (IVIG) allowed to achieve a complete control of the clinical picture. The frequency of IVIG administration and the dosage was progressively reduced. At the age of 9 she experienced Varicella Zoster Virus (VZV) reactivation followed by the recurrence of the inflammatory phenotype complicated by HLH with neurological involvement. Again, high-dose steroids and monthly IVIG resulted in a quick response. Targeted NGS for autoinflammatory diseases and immunodeficiencies revealed the homozygous Leu141Pro ADA2 mutation, that was confirmed by Sanger analysis. ADA2 enzymatic test showed a complete loss of ADA2 activity. For about 3 years IVIG alone were completely effective in preventing flares of inflammation and neurological manifestations. Anti-TNF treatment was started at the age of 13 for the appearance of recurrent genital ulcers, with a complete response. This case further expands the clinical spectrum of DADA2 and emphasizes the importance of extensive genetic testing in clinical phenotypes characterized by persistent unspecific inflammatory syndromes. Use of high doses IVIG might represent a possible effective immune-modulator, especially in combination with anti-TNF treatment.